Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Komik Pada Materi Bangun Ruang Untuk Meningkatkan Hasil Belajar Matematika - Firmansyah, Editya Yoga; Masriyah, Masriyah (MATHEdunesa, 2024)
This study aims to describe the validity, practicality and effectiveness of student worksheets based on comics on geometric materials developed in learning to improve student learning outcomes. The research method used in this study is a research and development. The subject of this research was a class of VII grade junior high school students. The instruments used were media expert validation questionnaires, material expert validation questionnaires, observation sheets of teachers' ability to manage learning, observation sheets of student activities, student response questionnaires and pretest-posttest.Based on the results of data analysis, it was found that the validation results of comic-based student worksheets were assessed by two validators, namely 1) media expert validator, 2) material expert validator. The results of the validation analysis of the experts obtained a score of 3. Based on the results of the validation analysis, comic-based student worksheets were developed that were feasible to try out. The results of observing the teacher's ability to manage learning obtained a score of 4, or included in the very good category. The results of observations of student activity obtained a score of 87.5%, or included in the active category. Based on the results of the practicality analysis, comic-based student worksheets are stated to be practical in the learning process. The results of the students' responses obtained a score of 96.57%, or included in the very good category. The pretest-posttest results obtained an N-gain score of 0.77, or included in the high category. Based on the results of the effectiveness analysis, comic-based student worksheets were declared effective in improving student learning outcomes.